Mittlere Schwingungsamplituden von SF₅Cl und SeF₅Cl - Baran, Enrique José (1976)
Mean amplitudes of vibration for SF₅Cl and SeF₅Cl have been calculated from spectroscopic data in the temperature range between 0 and 1000 K. The results are briefly discussed in comparison with those of related species. Some aspects concerning the bond properties of the two molecules are also analyzed.